Has Education in the United Kingdom Become a Marketable Product Like Other Value-Added Services? - Louise Dalingwater (Revue LISA)
The transformation of industry, with the shift from a manufacturing to a more service-oriented economy, has been particularly pronounced in the United Kingdom, with a rapid decline of the former and rise of the latter, notably from the 1960s onwards. However, the structural changes that have taken place are a little more complex than a disinvestment in one sector in favour of another. The two sectors are inextricably linked. In the same way, the distinction between public and private services has also become blurred and this is particularly the case in the education sector. The conventional perception of education as a public service, with public good attributes, has been challenged in recent decades in the United Kingdom. Education is now one of Britain’s major exports along with other high value-added services, such as finance and business services. The rise of neo-liberalism from the late 1970s and the increasing internationalization of the British economy have certainly challenged the traditional notion of education as a public good. Government policy has also been a key factor in the transformation of education towards a marketed service. The focus of this paper will be higher education because it is here that the marketed and non-marketed nature of educational services is most debatable. After considering conceptual issues, this paper will describe the transformation of educational services to show the extent to which this sector has become marketised in the United Kingdom.